Subtraia z1 = 12 – 3i e z2 = 15 + 2i
Soluções para a tarefa
Respondido por
1
Explicação:
z1 - z2 = 12 - 3i - (15 + 2i)
z1 - z2 = 12 - 3i - 15 - 2i
z1 - z2 = 12 - 15 - 3i - 2i
z1 - z2 = -3 - 5i
Respondido por
0
Resposta:
z1 - z2 = -3 - 5i
Explicação:
z1 - z2 = 12 - 3i - (15 + 2i)
z1 - z2 = 12 - 3i - 15 - 2i
z1 - z2 = 12 - 15 - 3i - 2i
z1 - z2 = -3 - 5i
Perguntas interessantes
Matemática,
9 meses atrás
Geografia,
9 meses atrás
Português,
9 meses atrás
Matemática,
1 ano atrás
Biologia,
1 ano atrás
Biologia,
1 ano atrás
História,
1 ano atrás
Biologia,
1 ano atrás